2001
DOI: 10.1001/jama.285.2.190
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Survival Following Early Revascularization for Cardiogenic Shock

Abstract: For patients with AMI complicated by CS, ERV resulted in improved 1-year survival. We recommend rapid transfer of patients with AMI complicated by CS, particularly those younger than 75 years, to medical centers capable of providing early angiography and revascularization procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
151
0
10

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 584 publications
(168 citation statements)
references
References 13 publications
7
151
0
10
Order By: Relevance
“…The primary endpoint (all-cause mortality at 30 days) did not differ between the initial medical stabilisation and early revascularisation treatment groups; however, there was a significant decrease in mortality rates at 3 and 6 years in patients assigned to early revascularisation. 14,17,18 The number needed to save one life at 1 year by early revascularisation in comparison with initial medical stabilisation is less than eight, and this benefit remained with long-term follow-up.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The primary endpoint (all-cause mortality at 30 days) did not differ between the initial medical stabilisation and early revascularisation treatment groups; however, there was a significant decrease in mortality rates at 3 and 6 years in patients assigned to early revascularisation. 14,17,18 The number needed to save one life at 1 year by early revascularisation in comparison with initial medical stabilisation is less than eight, and this benefit remained with long-term follow-up.…”
mentioning
confidence: 99%
“…However, the overall benefit of revascularisation in cardiogenic shock may extend past the traditional 12-hour window to potentially 54 hours post-MI and 18 hours after the onset of shock. 18,19 In current European Society of Cardiology (ESC) guidelines, early revascularisation by either PCI or CABG for cardiogenic shock is recommended, 20 but despite a general increase in the trend to perform early revascularisation, real-world rates remain relatively low (50-70 %). 2,14,21 Anti-platelet and Anti-thrombotic Medication…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…8 Recently, the SHOCK trial showed that early revascularization with a high utilization of IABP led to a significant improvement of 6-month and 1-year mortality rates. 9,10 In the 23 180 patients in the National Registry of Myocardial Infarction 2 (NRMI-2) with cardiogenic shock, the use of IABP in conjunction with thrombolytic therapy decreased the odds of death by 18%. 3 The outcome of selected medical procedures is increasingly associated with hospital and operator volume, particularly in the setting of coronary artery bypass graft (CABG) surgery.…”
mentioning
confidence: 99%